A PERANCANGAN RENCANA ANGGARAN BIAYA (RAB) PEMBANGUNAN RUMAH BERBASIS WEB METODE AHSP STUDI KASUS (PT PLATINDO INTI JAYA PUTRA) - Muhammad Naufal Murtado Naufal (JUPIK : Jurnal Penelitian Ilmu komputer, 2023)
The rapid development of Information Technology has penetrated all fields, including the construction services business. In this case the calculation of the calculation of the RAB budget plan. The RAB. program which in presenting information is still less attractive is replaced by implementing internet technology to facilitate the presentation of more interesting and dynamic information. This study aims to create a system for calculating the budget plan for house construction costs using a web application that is better in presenting calculations, processing data and exchanging user data. The waterfall method is a method of developing information systems at this stage. early stage.